Translating the Cognitive Model of PTSD to the Treatment of Very Young Children: A Single Case Study of an 8‐Year‐Old Motor Vehicle Accident Survivor. Issue 5 (May 2017) - Goodall, Benjamin; Chadwick, Isobel; McKinnon, Anna; Werner‐Seidler, Aliza; Meiser‐Stedman, Richard; Smith, Patrick; Dalgleish, Tim
Abstract : Posttraumatic stress disorder (PTSD) is a clinical condition that occurs after a discrete traumatic event, such as an accident or assault. Research into PTSD has primarily been adult‐focused; however, there is a growing body of evidence evaluating the theory and treatment of PTSD in young children. Consequently, cognitive behavior therapy (CBT) interventions for PTSD in youth have been developed that focus on 3 core components of the cognitive model–a disorganized memory of the trauma, maladaptive appraisals of the trauma and its effects ( meanings ), and dysfunctional coping mechanisms ( management ). Here, we describe the extension of this treatment approach (termed CBT‐3M) to very young children (3–8 years) through the case of Dylan, an 8‐year‐old motor vehicle accident survivor. This serves as an illustration of the underlying theory and its successful application. Further work is intended to provide evidence of the efficacy of this treatment via an ongoing treatment trial.